PERAN PEREMPUAN DALAM PENGEMBANGAN USAHA MIKRO DAN PENINGKATAN PENDAPATAN KELUARGA DI DESA KUTUH KABUPATEN BADUNG - Putu Ratna Windusara Putri; Ni Luh Wulani Parwati; Anak Agung Istri Setiari Jmh; I Made Sujana (Yayasan Nusantara Hasana Berdikari, 2022)
Women play a strategic role in strengthening household economies through their participation in micro-enterprises. This study aims to analyze the role of women in micro business development and their contribution to increasing family income in Kutuh Village, Badung Regency. The research employed a qualitative descriptive approach through observation, interviews, and documentation involving women entrepreneurs engaged in culinary businesses, handicrafts, trade, and tourism-supporting activities. The findings indicate that women significantly contribute to household income, business sustainability, and local economic development. Women entrepreneurs not only function as income earners but also as household financial managers and economic decision-makers. Factors supporting business development include access to local markets, tourism growth, family support, and entrepreneurial motivation. However, limited capital, marketing networks, and digital business skills remain major challenges. The study concludes that empowering women through entrepreneurship training, digital literacy enhancement, and financial access support can improve micro-enterprise performance and family welfare in Kutuh Village.